The starfish sisters : a novel - O'Neal, Barbara, 1959- (Lake Union Publishing, 2023)
"Phoebe and Suze used to be closer than sisters. Growing up in a quiet and wildly beautiful coastal town in Oregon, they shared everything. Until the secrets they couldn't share threatened their bond and complicated their lives. Now, decades later, Suze, a famous actress desperate for safe haven following a brutal attack, is back in town. Phoebe, a successful illustrator and fabric designer, has discovered keeping a secret means she can't let anyone get close, aside from her beloved granddaughter, Jasmine. As Jasmine's move to London looms, Phoebe doesn't know how to face the return of her old friend and all that's still unsaid between them. Can the two women who've never confronted their past do it now when the choice is between healing and survival?"--